2014
DOI: 10.15252/embj.201489039
|View full text |Cite
|
Sign up to set email alerts
|

The small GTPase Arf1 modulates mitochondrial morphology and function

Abstract: The small GTPase Arf1 plays critical roles in membrane traffic by initiating the recruitment of coat proteins and by modulating the activity of lipid-modifying enzymes. Here, we report an unexpected but evolutionarily conserved role for Arf1 and the ArfGEF GBF1 at mitochondria. Loss of function of ARF-1 or GBF-1 impaired mitochondrial morphology and activity in Caenorhabditis elegans. Similarly, mitochondrial defects were observed in mammalian and yeast cells. In Saccharomyces cerevisiae, aberrant clusters of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
128
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(139 citation statements)
references
References 93 publications
9
128
1
1
Order By: Relevance
“…Furthermore, ARF1 was shown to genetically interact with GEM1; specifically, loss of Gem1 exacerbated the mitochondrial morphological phenotype associated with the arf1 mutant. These results suggested that Arf1 regulates ERMES functions, such as mitophagy [5]. However, it should be noted that Arf1 does not appear to be required for the physical tethering between the ER and mitochondria via ERMES.…”
mentioning
confidence: 89%
“…Furthermore, ARF1 was shown to genetically interact with GEM1; specifically, loss of Gem1 exacerbated the mitochondrial morphological phenotype associated with the arf1 mutant. These results suggested that Arf1 regulates ERMES functions, such as mitophagy [5]. However, it should be noted that Arf1 does not appear to be required for the physical tethering between the ER and mitochondria via ERMES.…”
mentioning
confidence: 89%
“…Previous reports have demonstrated that loss of ARF1 impaired mitochondrial morphology in mammalian and yeast cells . Herein, we observed mitochondrial morphology in the arf1 Δ/Δ cells with MitoTracker Red staining.…”
Section: Resultsmentioning
confidence: 61%
“…GFB-1 and SGK-1 physically associate, being GBF-1 required for proper localization of SGK-1 near the basolateral membrane of intestinal cells [62]. Interestingly, ARF1 and GBF1 play an evolutionarily conserved role in ER-mitochondria contact site functionality and lack of GBF-1 causes a similar increase in mitochondrial size as sgk-1 deletion in C. elegans ([83] and Figure 1B and S1).…”
Section: Resultsmentioning
confidence: 99%